Strategy of Cultural Adaptation of Foreign Teachers in Multicultural Classrooms at Springfield - Halim, Laurin Violentika; Murtiningsih, Bherta Sri Eko; Juliadi, Rismi (ULTIMA Comm, 2024)
The cultural differences between foreign teachers and local students in multicultural classrooms impact teaching methods, communication styles, student-teacher interactions, and teaching preferences, affecting the effectiveness of learning. Studies on culture and educational communication in these settings are limited. This study investigates the cultural adaptation strategies of foreign teachers in multicultural classroom environments at Springfield High School. Utilizing Young Yun Kim's cultural adaptation theory framework, this research explores how foreign teachers at Springfield High School, an Indonesian school with an international curriculum, adjust in a collective educational setting, through a qualitative approach involving interviews with three participants and direct observations, employing a descriptive case study method. The findings highlight that foreign teachers' cultural adaptations involve key factors such as empathy, openness, flexibility, and support from the school environment. The model of cultural adaptation identified in this research is acculturation. This study contributes to the field of cross-cultural educational communication by emphasizing that foreign teachers need to understand the cultural backgrounds of local students to foster positive and meaningful interactions that enhance learning. The implications of this research include guiding the development of intercultural training programs designed to support foreign teachers and improve educational outcomes in multicultural classrooms. It underscores the importance of cultural competence among teachers working in these diverse environments.